Chicken Infectious Anaemia Virus: A Mini-Review - A. I. Alkateb, E. K. Gerish (Journal of Pure & Applied Sciences, 2019)
Chicken Infectious Anaemia Virus (CIAV), also known as Chicken Anaemia Agent (CAA) or CAV Chicken Anaemia Virus, is the smallest DNA virus classified in the genus Gyrovirus of the family Circoviridae. Since its first identification in 1979 by Yuasa and his colleagues,  CIAV is a virus non- enveloped, stable and very resistant to the environment and disinfectants, it has a simple circular DNA chain. All CIAV strains are known until now belong to the same serotype, which means that there are no major antigenic differences, although there may be diversity in the genome of the virus. CIAV has caused great economic losses for the poultry industry, due to its serious immunosuppressive potential and ability to predispose to multiple secondary bacterial infections, subsequently playing a key role in the aetiology of several multifactorial diseases, immune suppression and the production of antibodies for chicken infectious anaemia in field challenge. Along with notable characteristics such as vertical/horizontal transmission, ubiquitous, contagiousness, resistance and propagated nature. The poultry industry needs the immunization of the breeding birds, in order to avoid the horizontal transmission of the virus and provide maternal antibody titers that give massive protection to the progeny. This review presents an updated comprehensive overview on CIAV.